THE VALUES OF PEACE EDUCATION IN THE PERSPECTIVE OF THE HOLY QUR'AN - Hadisaputra, Prosmala; Farhan, Lalu Pattimura; Tengku Kasim, Tengku Sarina Aini; Yussuf, Ahmad (Journal of Islamic Educational Research, 2020)
This article is the result of a literature review. This study aims to explore the values of peace education in the Holy Qur'an. To ensure the authenticity of this paper, we explore themes related to peace education through Google Scholar. In our search, we found 2,950,000 results. Then we do the restrictions with keywords, year, and all keywords are collected in the title of the article. From the restrictions we did, we found 1,210 results. Then we add restrictions, namely by specifying the keyword to “peace education, Islam." From the additional restrictions, we get eight articles that focus on talking about peace education in Islamic education. Finally, we specify a search with the keyword “peace education, al-Qur’an and hadith,” the search results are zero. Therefore, we decided to focus on discussing the values of peace education in the Holy Qur'an. We concluded that al-Qur'an emphasizes peace is proven with more significant verses of peace than war verses, as we can explore in the book of al-Mu'jam al-Mufahras fi Alfaz al-Qur'an al-Karim. This study also found that the values of peace education in the Qur'an were at least four, namely: 1) tolerance (tasamuh); 2) polite dialogue; 3) cooperation (al-ta'awun); and 4) forgiving (al-'afw).